Combined numerical and experimental estimation of the fracture toughness and failure analysis of single lap shear test for dissimilar welds. (15th May 2021) - Jimenez-Mena, Norberto; Sapanathan, Thaneshan; Jacques, Pascal J.; Simar, Aude
Highlights: Fracture toughness of dissimilar weld with intermetallics layer (IMC) is estimated. Two welding processes were used to get Al/steel welds with various microstructures. IMC thicknesses and heterogeneous hardness variations were feed to the FE models. Fracture toughness of the weld is three time higher than that of the intermetallic. Simulation reveals that crack propagation rely on the plasticity of base metals. Abstract: The single lap shear test is widely used to measure the strength of dissimilar welds even though such a test brings limited understanding of the intrinsic weld toughness. The present study proposes a numerical finite element (FE) analysis and experimental characterization of dissimilar joints presenting various microstructures (thickness of the intermetallic layer (IML) and hardness profile). For this purpose, Friction Melt Bonding (FMB) and Friction Stir Welding (FSW) were used to join aluminum AA6061 and Dual Phase steel (DP980). The FE simulations allowed calculating the evolution of the J -integral near this notch tip. It shows that crack initiation depends significantly on the plastic properties of the welded metallic alloys around the notch tip and the width of the welded zone, which both are significantly different for FSW and FMB processes. Nevertheless, a similar weld fracture toughness J C of approximately 1 kJ.m −2 is estimated from the analysis for both FMB and FSW. This is three orders of magnitude higher than the fracture toughness of the intermetallic layer, revealing that the plastic dissipation in the Al and steel plates around the crack tip has a major effect on the weld toughness.